2021
DOI: 10.3390/cells10040803
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting and Differentiation of Adipose-Derived Stromal Cell Spheroids for a 3D Breast Cancer-Adipose Tissue Model

Abstract: Biofabrication, including printing technologies, has emerged as a powerful approach to the design of disease models, such as in cancer research. In breast cancer, adipose tissue has been acknowledged as an important part of the tumor microenvironment favoring tumor progression. Therefore, in this study, a 3D-printed breast cancer model for facilitating investigations into cancer cell-adipocyte interaction was developed. First, we focused on the printability of human adipose-derived stromal cell (ASC) spheroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 66 publications
0
64
2
Order By: Relevance
“…A good scaffold for hard tissue engineering should have approximately 100–400 µm of well-interconnected pores to support good tissue regeneration and the addition of CA into MTA did not affect such desired characteristics of the scaffolds. The 3D microenvironment was able to adopt proper structures and cellular interactions, and allow nutrient perfusion to all levels and thus is commonly used for modeling mechanisms of normal physiological processes, tumor biology, tissue regeneration and monitoring of treatment efficacy [ 28 , 29 ]. This initial screen showed that the design of our scaffolds was able to withstand mechanical loading and forces typically experienced during implantation and at the scaffold–tissue interface.…”
Section: Resultsmentioning
confidence: 99%
“…A good scaffold for hard tissue engineering should have approximately 100–400 µm of well-interconnected pores to support good tissue regeneration and the addition of CA into MTA did not affect such desired characteristics of the scaffolds. The 3D microenvironment was able to adopt proper structures and cellular interactions, and allow nutrient perfusion to all levels and thus is commonly used for modeling mechanisms of normal physiological processes, tumor biology, tissue regeneration and monitoring of treatment efficacy [ 28 , 29 ]. This initial screen showed that the design of our scaffolds was able to withstand mechanical loading and forces typically experienced during implantation and at the scaffold–tissue interface.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Horder et al . have interrogated the interaction between adipose-derived stromal cell (ASC) and breast cancer cells in a 3D-printed co-culture model[ 122 ]. The model was composed of directly printed ASC spheroids in hyaluronic acid (HA)-rich hydrogel.…”
Section: 3d Printing-assisted Spheroid Assemblymentioning
confidence: 99%
“…Horder et al demonstrated remodeling of the adipose tissue ECM and tumor cell-induced modulation of the lipid content when co-cultured with breast cancer cells by using a 3D printed tissue construct with MDA-MB-231 cells in combination with ASC spheroids. Results showed an increase in fibronectin, collagen I, and collagen VI expression, demonstrating that 3D model systems more accurately represent the complexity of the cellular and matric cross talk within the tumor-stroma microenvironment ( Horder et al, 2021 ). More recently, these 3D spheroids are used in combination with engineered 3D printed scaffolds using biodegradable materials.…”
Section: Ascs In Novel Laboratory Models Of Breast Cancermentioning
confidence: 99%
“…Biotechnology and fabrication have recently emerged as a superior approach to creating microphysiological systems in order to study different diseases in the human body, especially cancer. Because human tissues are organized in a complex 3D structure with cellular-ECM cross talk, 3D bioprinting allows for the design of a complex architecture with placement of the cellular components in physiological spatial micro-arrangements ( Horder et al, 2021 ). Many different approaches can be taken to create 3D bioprinted cellular models: Individual cells can be printed in hydrogel-based inks, multicellular aggregates, such as spheroids, and complex engineered 3D constructs that mimic microtissues can be bioprinted ( Benmeridja et al, 2020 ; Levato et al, 2020 ).…”
Section: Ascs In Novel Laboratory Models Of Breast Cancermentioning
confidence: 99%